Marginalized Literature - Ravindra Kumar Singh; Usha Sawhney (Integrated Journal for Research in Arts and Humanities, 2022)
Introduction manages the foundation of Indian English Novel. It follows the development of Indian English Fiction in order to place this theory in appropriate point of view. An Indian English epic consistently has given cognizant voice to the enduring segment of the general public. Right now, endeavor is made to make a study of the commitment of Indian English writer to make this type wealthy in quality and amount. The section centers around how Indian authors have purchased name and popularity to Indian English papers. It centers around the commitment of Mulk Raj Anand, Rohinton Mistry, Arundhati Roy and Manju Kapur have given conscious voice to the marginalized area of the general public.